2015
DOI: 10.1097/mib.0000000000000273
|View full text |Cite
|
Sign up to set email alerts
|

Accuracies of Serum and Fecal S100 Proteins (Calprotectin and Calgranulin C) to Predict the Response to TNF Antagonists in Patients with Crohnʼs Disease

Abstract: Serum S100A12 level and fCal are reliable markers associated with response to induction therapy with anti-TNF. Fecal calprotectin was the best for predicting clinical remission in CD under maintenance therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 19 publications
6
64
0
1
Order By: Relevance
“…In our study, one patient was excluded due to a diagnosis of IBD, but none of the other participants underwent ileocolonoscopy because of a lack of clinical symptoms. Although the increased CRP and serum calprotectin appear to be predictive markers for intestinal involvement in SpA [41] and faecal calprotectin is a well-known marker of IBD activity [54], there is no correlation between serum and faecal calprotectin [41, 55]. A beneficial effect of mild exercise on the course of IBD has been suggested [56], but the relationship between intestinal inflammation and axSpA disease activity and progression in respect to physical activity requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, one patient was excluded due to a diagnosis of IBD, but none of the other participants underwent ileocolonoscopy because of a lack of clinical symptoms. Although the increased CRP and serum calprotectin appear to be predictive markers for intestinal involvement in SpA [41] and faecal calprotectin is a well-known marker of IBD activity [54], there is no correlation between serum and faecal calprotectin [41, 55]. A beneficial effect of mild exercise on the course of IBD has been suggested [56], but the relationship between intestinal inflammation and axSpA disease activity and progression in respect to physical activity requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…High FC at baseline have been associated with increased risk of disease relapse among patients with CD, 24 while FC levels that normalize after induction therapy have been associated with sustained clinical remission among patients with CD and UC. 133,134 Lower FC levels have been associated with response to biologic therapy and clinical outcomes including clinical remission and mucosal healing. 135,136 Perhaps most useful, among patients in remission, FC has been reported to increase earlier and remain elevated prior to clinical or endoscopic relapse of disease, 137 which may indicate a role for prospective or routine monitoring with FC to identify those patients at greatest risk of relapse.…”
Section: Future Directions For Biomarkersmentioning
confidence: 99%
“…Fecal S100A12 is significantly increased in severe acute pediatric UC patients and decreases gradually when children are under clinical remission, but does not correlate with the therapeutic response (45). A recent study showed that the fecal S100A12 level is a reliable tool associated with the response to anti-TNF therapy of IBD (46). In addition to IBD, however, S100A12 is also increased in other inflammatory diseases, such as arthritis and Kawasaki disease (47, 48) (Table 1).…”
Section: I- Currently Available Biomarkersmentioning
confidence: 99%